2009
DOI: 10.2214/ajr.07.3952
|View full text |Cite
|
Sign up to set email alerts
|

Angioleiomyoma in Soft Tissue of Extremities: MRI Findings

Abstract: Angioleiomyoma should be considered a possible diagnosis when a well-demarcated subcutaneous mass of isointense signal on T1-weighted images, heterogeneous high signal intensity on T2-weighted images with homogeneous strong enhancement, and an adjacent tortuous vascular structure is seen in the extremities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
56
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 8 publications
5
56
2
Order By: Relevance
“…10 Pain is the most common presenting symptom in patients with angioleiomyoma, reported in 58% of patients from a series by Hachisuga et al 7 The pain is thought to be related to local ischemia resulting from smooth muscle contraction. 4 There are 3 categories of vasculature patterns in an angioleiomyoma: type 1, several clustered linear vessels that converge to a single point; type 2, scattered distribution of irregular vessels; and type 3, vessels (1 or more) that are centrally located. 2 Vasculature is further classified as little (covering less than 20% of the mass), moderate (20%-50%), and rich (N 50%) vasculature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Pain is the most common presenting symptom in patients with angioleiomyoma, reported in 58% of patients from a series by Hachisuga et al 7 The pain is thought to be related to local ischemia resulting from smooth muscle contraction. 4 There are 3 categories of vasculature patterns in an angioleiomyoma: type 1, several clustered linear vessels that converge to a single point; type 2, scattered distribution of irregular vessels; and type 3, vessels (1 or more) that are centrally located. 2 Vasculature is further classified as little (covering less than 20% of the mass), moderate (20%-50%), and rich (N 50%) vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 The mass can be dermal or subcutaneous, or may occur in the superficial fascia of the extremities. 4 Pain is documented as a primary concern in 60% of patients. [4][5][6] Three subdivisions www.journalchiromed.com of angioleiomyoma exist: solid, cavernous, and venous, with solid being the most common.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yoo et al 11 suggested that the presence of tortuous vascular channels surrounded by smooth muscle bundles and areas of myxoid change could explain the heterogenicity of signal intensity of the tumor on T2-weighted images. Matsuyama et al 12 reported that some flow void is suggestive of vessels along and/or within the tumor and can help in the diagnosis of angioleiomyoma.…”
Section: Discussionmentioning
confidence: 99%
“…CT features consist of homogenous soft tissue mass with homogenous contrast enhancement. Regarding MRI, these tumors are most commonly isointense on T1-wighted images, heterogenous high signal intense on T2-weighted images, and have a homogenous strong enhancement [10].…”
Section: Discussionmentioning
confidence: 99%